2020
DOI: 10.1002/mc.23183
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic cell death in colon cancer prevention and therapy

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related death worldwide. The colonic mucosa constitutes a critical barrier and a major site of immune regulation. The immune system plays important roles in cancer development and treatment, and immune activation caused by chronic infection or inflammation is well-known to increase cancer risk.During tumor development, neoplastic cells continuously interact with and shape the tumor microenvironment (TME), which becomes progressively immunosuppressive. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 172 publications
(328 reference statements)
0
66
0
Order By: Relevance
“…Incidence and mortality rates of CRC are elevating in majority of the Asia-Pacific area, predominantly due to mounting urbanization and industrialization of countries and communities ( Ku et al, 2012 ). The immune system functions importantly in cancer progression and treatment, and immune response induced by chronic infection and inflammation may enhance the risk for cancers ( Ruan H. et al, 2020 ). Meanwhile, natural killer (NK) cells are a group of cells that could eliminate tumor cells and the release of cytokines, and NK cell-regulated production of interferon gamma (IFN-Îł) is well known for its antiviral, immunoregulatory, as well as anti-tumor properties ( Cui et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence and mortality rates of CRC are elevating in majority of the Asia-Pacific area, predominantly due to mounting urbanization and industrialization of countries and communities ( Ku et al, 2012 ). The immune system functions importantly in cancer progression and treatment, and immune response induced by chronic infection and inflammation may enhance the risk for cancers ( Ruan H. et al, 2020 ). Meanwhile, natural killer (NK) cells are a group of cells that could eliminate tumor cells and the release of cytokines, and NK cell-regulated production of interferon gamma (IFN-Îł) is well known for its antiviral, immunoregulatory, as well as anti-tumor properties ( Cui et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that mutant KRAS cooperates with p-4E and Myc to promote ISR-dependent Gln addiction, which is characterized by increased cell death, transcriptional heterogeneity, and surprisingly immune suppression upon deprivation. Hyperactivation of Wnt/Myc and mutant RAS/RAF are strongly associated with cancer aggressiveness including immunosuppressive TME, absence of TILs, and resistance to immune checkpoint inhibitors ( Ruan et al, 2020 ). Our data provide direct evidence that p-4E rewired translation and stress response is involved in this process through increased entropy or chaos ( Tarabichi et al, 2013 ; Hanselmann and Welter, 2016 ) and target selection during chronic metabolic adaptation and competition within tumor cells and with the TME ( Palm and Thompson, 2017 ; Andrejeva and Rathmell, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myc, mutant RAS/RAF, or PIK3CA fuels abnormal growth by altering nutritional needs, including increased glutamine utilization. However, direct targeting a single driver, a single metabolic step, p-4E, or p-4E-BP1 has limited success in the clinic so far, due to complex resistance mechanisms encompassing compensatory pathway activation, metabolic bypasses, apoptosis resistance and immune suppression ( Dang et al, 2017 ; Pelletier et al, 2015 ; Truitt and Ruggero, 2016 ; Palm and Thompson, 2017 ; Ruan et al, 2020 ; Lito et al, 2013 ; Zhang and Yu, 2013 ). Our model supports that Myc-driven metabolic addiction likely goes beyond Gln to other nutrients and reducing agents such as arginine, cystine, and glutathione necessary to support increased biosynthesis ( Figure 7F ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for patients with advanced CRC, the major interest is for new therapies and prognostic perspectives which are based on biological neoplastic features [5,13]. Recently, the utility of 'tailored therapy' has been proven in many studies, based on the fundamental paradigm that patients respond to biological therapies in different ways [27,28]. The term 'tailored therapy' is used to indicate a treatment based on patients' individual characteristics and specific cancer's histological pattern [8].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%